Additions to the centipede (Chilopoda) fauna of the Maltese Islands, with new distributional records and an updated checklist - Thomas Cassar (Senckenberg Gesellschaft für Naturforschung, 2021)
Three chilopod species are recorded as new for the Maltese archipelago, and two species are recorded for the first time from the island of Comino. The local distribution of previously-recorded species is updated with new data. A check-list of the twenty-five species occurring on the islands is also provided.